Pendampingan Pembuatan dan Aplikasi Herbal Probiotik untuk Budidaya Ikan Lele pada Pokdakan RSB Fisheries Family - Hardi, Esti Handayani; Agriandini, Maulina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2024)
The regional and national governments want fish farming to boost the community's income. A tarpaulin tank catfish farming demonstration plot was provided by the Indonesian Ministry of Maritime Affairs and Fisheries to Pokdakan RSB Fisheries Family. Freshly stocked catfish seeds died 100% during growing. Mulawarman University trains and assists Pokdakan in using probiotic herbs to promote catfish seed resilience and growth. On March 23–24, 2024, the Pokdakan Cultivation Pond will host this event. The program begins with an introduction to herbal medicine and fish probiotics, then covers how to create them, how to use them in catfish farming, and survival and growth monitoring. The exercise involved 10 Pokdakan members. This course helps Pokdakan freshwater fish farmers understand the varieties and benefits of herbs and probiotics, their dosage and how to soak and combine them with feed, and how to monitor and diagnose early sickness in catfish fry. Following 2.5 months of maintenance, this activity reduces seed mortality from 100% to 20%, yielding an average harvest weight of 100 g/head.